Transitional Justice in Post-Conflict Countries: The “Arab Spring” States as a Model - Mustafa Hussein Abdelbaqi (دراسات: علوم الشريعة والقانون, 2020)
Transitional justice is "the set of strategies, programs, mechanisms and judicial and non-judicial procedures that are followed in order to understand and address the past of human rights violations, by revealing their truth, accountability and accountability of those responsible, reparation and rehabilitation of victims, in order to achieve national reconciliation, preserve and document the collective memory, establish guarantees of non-recurrence of violations, and move from a state of tyranny to a democratic system that contributes to the consolidation of the human rights system". The need for transitional justice usually arises after civil wars when traditional justice is unable to carry out the functions of the administration of justice, due to its weak and corrupt institutions. The philosophy of transitional justice is based on restoring citizens ' trust in the state. Transitional justice is a special type of justice, although it shares objectives with traditional justice. Transitional justice mechanisms vary from state to state and from experience to experience, but can be reduced to three ways: investigation and criminal prosecution; fact-finding (truth commissions); and reparation and compensation for victims. The study reached several results, including: the philosophy of transitional justice is based on restoring the confidence of citizens in the state. To overcome self-fulfilling crimes, civil wars, terrorism transitional justice must be used.